PEMETAAN POTENSI PENGEMBANGAN NAGARI TALANG BABUNGO KABUPATEN SOLOK SEBAGAI DESTINASI WISATA RURAL - Abdiani Khairat Nadra (Jurnal Pariwisata Bunda, 2022)
Rural tourism is a type of tourism that has the potential to be developed because it is part of quality and sustainable tourism and is becoming a world tourism trend because it offers an authentic holiday experience in a relaxed and healthy environment. Many rural areas in West Sumatra have the potential to be developed into new tourist attractions, Nagari Talang Babungo which is located in Hiliran Gumanti District, Solok Regency has diverse and interesting tourism potential to be developed, but still requires a lot of effort and strategy to advance it. data collection was carried out by observating and in-depth interviews with several relevant informants as well as documentation studies. Data analysis was carried out through four stages from data collection, data reduction, data presentation, and drawing conclusions and verification, the data that has been collected will be analyzed using the SWOT analysis. The results of the research show that Nagari Talang Babungo has the potential to be developed into a rural tourism destination by implementing the right strategy in the future so that Talang Babungo can be developed by applying appropriate strategies.